Evaluation and application of SCAR markers on BAP-induced dwarf off-types of Musa Acuminata cv. berangan / Arifurrahman bin Rusman - Rusman, Arifurrahman (2012)
Micropropagation has been widely used to produce better crops at a rapid rate. Plant growth regulators are used to increase shoot proliferation, with benzylaminopurine (BAP) being the most commonly used cytokinin. However, various studies have shown that BAP concentration affects the frequency of abnormality in banana micropropagation. For this study, the effects of BAP concentrations on in vitro cultures of Musa acuminata cv. “Berangan” were investigated and it was found that on Murashige and Skoog (MS) media supplemented with concentrations of 9mgL-1 and 12mgL-1 BAP, cultures took a longer time to regenerate as compared to concentrations of 3mgL-1 and 6mgL-1. Abnormalities such as having abnormal shoot clusters and remaining in an undifferentiated callus state were also observed on cultures of the higher BAP concentrations. Dwarf SCAR markers developed by Damasco et al. (1996) were used to analyze the genomic changes of the in vitro cultures via polymerase chain reaction. A single band of about 1.6kb present only on normal plants and absent in dwarfs would have been expected. However, instead of the predicted 1.6kb single band, two bands of 662bp and 438bp in length were observed regardless of the morphology of the regenerants produced (normal or stunted). A BLAST analysis of the 662bp sequence did not reveal any homologous fragment but the 438bp sequence was found to be homologous to fragments of the Musa acuminata clone BAC MA4-3F3. Initially found to be hypothetical proteins, a further BLAST analysis using the banana genome revealed that these proteins would presumably be present in chromosome 6 and identified as the ubiquitin-fold modifier 1.